Daprodustat for anemia: a 24-week, open-label, randomized controlled trial in participants on hemodialysis - Meadowcroft, Amy M (Clin Kidney J, 2018)
BACKGROUND: This study evaluated the hemoglobin dose response, other efficacy measures and safety of daprodustat, an orally administered, hypoxia-inducible factor prolyl hydroxylase inhibitor in development for anemia of chronic kidney disease. METHODS: Participants (n = 216) with baseline hemoglobin levels of 9–11.5 g/dL on hemodialysis (HD) previously receiving stable doses of recombinant human erythropoietin (rhEPO) were randomized in a 24-week dose-range, efficacy and safety study. Participants discontinued rhEPO and then were randomized to receive daily daprodustat (4, 6, 8, 10 or 12 mg) or control (placebo for 4 weeks then open-label rhEPO as required). After 4 weeks, doses were titrated to achieve a hemoglobin target of 10–11.5 g/dL. The primary outcome was characterization of the dose–response relationship between daprodustat and hemoglobin at 4 weeks; additionally, the efficacy and safety of daprodustat were assessed over 24 weeks. RESULTS: Over the first 4 weeks, the mean hemoglobin change from baseline increased dose-dependently from −0.29  (daprodustat 4 mg) to 0.69 g/dL (daprodustat 10 and 12 mg). The mean change from baseline hemoglobin (10.4 g/dL) at 24 weeks was 0.03 and −0.11 g/dL for the combined daprodustat and control groups, respectively. The median maximum observed plasma EPO levels in the control group were ∼14-fold higher than in the combined daprodustat group. Daprodustat demonstrated an adverse event profile consistent with the HD population. CONCLUSIONS: Daprodustat produced dose-dependent changes in hemoglobin over the first 4 weeks after switching from a stable dose of rhEPO as well as maintained hemoglobin target levels over 24 weeks.